The BankÄ±ng ResolutÄ±on Funds In The European UnÄ±on - Toth, Jozsef (European Scientific Journal, ESJ, 2016)
The new directive of the European Parliament and the European Council issued in 2014 define unified expectations regarding banking resolution mechanism to be applied in territory of each EU member state. The non-euro zone member states must create national resolution funds while the euro zone member states have to upload the so called Single Resolution Fund. These funds are implemented in order to finance the banking resolution processes. This article introduces the main rules of the unified resolution system as well as deals with its financial background. The European Commission declared in its statement that the target level of the Single Resolution Fund is 55 billion euros. However, this paper provides evidence that this target level is underestimated.